273 Project echo: 2-years experience in Belarus. (13th November 2020) - Matylevich, O; Shushkevich, A; Perevoschikov, P; Pletnev, A; Petukhov, V; Mavrichev, S; Plotkin, A; Gemer, O; Eiken, M; Ralph, S; Schmeler, K
Abstract : Objectives: Build expertise and competence in diagnostic and treatment of gynecological cancers among clinicians based in Belarus Cancer Centers via case-based analysis of patients by using videoconferencing technology to connect local care providers with world leading gynecologic oncologists, pathologists, and radiation oncologists. Methods: With support from MD Anderson Cancer Center in Texas, USA, IGCS began utilizing the Project ECHO model to conduct virtual tumor boards with trainees as part of the Global Curriculum & Mentorship Program. In late 2017, IGCS expanded Project ECHO and held the first session with the Belarusian Society of Oncology, a member of the IGCS Strategic Alliance Partnership. The sessions are held monthly by videoconference utilizing Zoom technology to link Faculty Consultants from USA, Canada, Australia, Israel with the clinicians in Minsk. Each Project ECHO session is one hour in length with 30–45 minutes of case presentations and discussion followed by a 15–30–minute didactic lecture. Results: The multidisciplinary team of IGCS participants for Belarus ECHO projects was created. Twenty-two ECHO meetings were held in the period 2017–2019. Belorussian clinical team presented 37 problem-based cases followed by discussion of the cases and a brief didactic lecture. The average number of participants per session was ten. Future developments of this ECHO project include introduction follow-up discussions of cases under review. Conclusions: Project ECHO in Belarus is a useful tool to support international clinical consulting opportunities that allow gynecologic oncologists in Belarus to receive best practice guidance from world leading specialists and provide up to date clinical management.